PENGARUH PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KEIAS XI MIPA SMA NEGERI 1 LUBUK ALUNG - INDAH ADITYA PUTRI (Jurnal Edukasi dan Penelitian Matematika, 2021)
The ability to solve mathematical problems is one of the objectives of learning mathematics that must be mastered by students. In fact, this problem solving ability is still low. This can be seen in the low test scores given to students which contain indicators of mathematical problem solving. The solution to this problem is to apply a realistic mathematics education approach. The purpose of this study was to describe the problem solving abilities of students in class XI MIPA of SMA Negeri 1 lubuk Alung 2020/2021 who learn to use a realistic mathematics education approach better than students who learn using direct learning. Keywords — Mathematical Problem Solving, Realistic Mathematics Education Approach, Direct learning Model.